Determinants Of Graduate Quality: Entrepreneurial Competence, Religious Culture, And Pedagogical Competence In Madrasah - Asari, Asari; Nafan Tarihoran; Apud (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to analyse and demonstrate the influence of entrepreneurial competence, religious culture, and pedagogical competence on graduate quality, as well as to describe an implementation model based on interview results. Employing a mixed-methods approach with an explanatory sequential design, this study involved State Madrasah Aliyah teachers in eight cities/regencies of Banten Province, Indonesia. A sample of 349 teachers was selected through proportional stratified random sampling. The results indicate that the entrepreneurial competence of Madrasah Principals (X1), religious culture (X2), and pedagogical competence (X3) significantly and simultaneously influence graduate quality (Y), with a p-value of .000 (p < .05). The R-squared value of 0.844 suggests that 84.4% of the variance in graduate quality can be explained by these three independent variables. Among these, pedagogical competence (X3) exhibits the strongest and most significant influence on graduate quality, as indicated by its t-value. To optimize the influence of these variables, the study recommends a transformational leadership approach to foster synergy between entrepreneurial leadership, religious culture, and teacher pedagogy. This approach can facilitate the development of innovative programs and policies that create meaningful learning experiences, ultimately producing graduates who are not only academically proficient and spiritually grounded, but also possess strong character and relevant skills to meet societal needs.